Principles of Formation of A Culture of Target Use of Youth Internet Resources - kizi, Khabibullaeva Irodakhon Dilshod (European Journal of Life Safety and Stability (2660-9630), 2021)
Today, the majority of the world's population uses the Internet. Man and society do not stand still, they are constantly changing, it has become commonplace to call the present we live in a period of globalization. Data transmission tools The development of the country has served to create a single information system that includes all countries. It is thanks to the Internet that local information networks are integrated into a single global network.